THE ROLE OF FARMING GROUP IN THE IMPLEMENTATION OF SAPTA BUSINESS IN PADDY RICE FARMING IN LADONGI SUB-DISTRICT LADONGI DISTRICT KOLAKA EAST DISTRICT - Sahrul Ramadhan; Awaluddin Hamzah; Tjandra Buana (Jurnal Ilmiah Inovasi dan Komunikasi Pembangunan Pertanian, 2023)
The paddy rice commodity, which is in high demand in the Ladongi Village and has a price that is regarded as more stable in the market than the fluctuating prices of other agricultural commodities, served as the inspiration for this study. The lowland rice farming group in Ladongi Village consists of 32 farmer groups, the majority of which have engaged in seven agricultural pursuits. The research aims to determine the role of lowland rice farmer groups and to determine the application of Sapta lowland rice farming in Ladongi Village, Ladongi District, East Kolaka Regency. This study used a quantitative descriptive method with proportional random sampling with a total sample of 42 people. The results of this study indicate that the role of lowland rice farmer groups in Ladongi Village has a good role as a learning class, a vehicle for collaboration, and a production unit. Then the application of sapta farming in Ladongi Village is included in the high category or has been carried out well. This can be seen from the height of the seven indicators of farming, namely superior seeds, land management, fertilization, pest and disease control, irrigation, harvesting, and post-harvest which have shown high application.